Efficacy and Safety of Low-Dose Nab-Paclitaxel Plus Tislelizumab in Elderly Patients With Previously Treated Metastatic Non-Small Cell Lung Cancer - Zhu, Wenyu; Geng, Qian; Peng, Haoliang; Jin, Zhihui; Li, Dongqing; Pu, Xiaolin; Wang, Ge; Jiang, Hua (Frontiers in Oncology, 2022)
The combination of immunotherapy and chemotherapy has a synergic effect in non-small cell lung cancer (NSCLC). However, the elderly are often excluded from clinical trails due to their poor health status and more comorbidities. We sought to assess the efficacy and safety of low-dose nanoparticle albumin-bound paclitaxel (nab-paclitaxel) plus tislelizumab (an anti-PD-1 antibody) in elderly patients with advanced NSCLC. In this phase 2 clinical trail, eligible patients were those aged ≥65 years with metastatic NSCLC who had disease progression after treatment with ≥1 line of chemotherapy or targeted therapy. Patients with epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) variations were eligible if they demonstrated disease progression after treatment with ≥1 corresponding inhibitor. Primary endpoints were progression-free survival and safety/tolerability. Secondary endpoints included objective response rate and overall survival. Among 29 patients enrolled from May 2019 through August 2020, 21 (72.4%) had adenocarcinoma, 17 (58.6%) had a performance status of 2, 8 (27.6%) had asymptomatic brain metastases, and 13 (44.8%) had EGFR/ALK variations. As of the data cutoff point on April 1, 2021, median progression-free survival and overall survival were 9.5 months and 16.5 months, respectively. Ten patients achieved a partial response (objective response rate of 34.5%). Seventeen (58.6%) patients had ≥1 treatment-related adverse event, with grade 3 events seen in 3 patients (10.3%). The most common adverse events were fatigue (20.7%), fever (17.2%), abnormal liver function (17.2%), and rash (17.2%). These results suggest that low-dose nab-paclitaxel plus tislelizumab is well tolerated and effective in elderly patients with advanced NSCLC, including those with EGFR/ALK variations.